Doing the Wild Thing: Supporting an Ordinary Sexual Life for People with Intellectual Disabilities - Hamilton, Carol (Disability Studies Quarterly, 2002)
For many people who are called disabled, having this label means to be excluded from the experience of 'an ordinary sexual life'. For those who are called intellectually disabled exclusion from experiences of any kind of positive sexual life is almost universal. This article explores how some people with intellectual disabilities have sought to open up pathways towards accessing experiences of sexual expression as a way to move forward towards being able to integrate a concept of sexuality into their lives. Two support workers are interviewed. Both are employed by a Human Services organization in Aotearoa, New Zealand, which provides long term support for people with intellectual disabilities. Their comments reveal that access to successful instances of sexual expression for people in this group are currently only available those who are articulate enough and persistent enough to keep trying until they succeed. Barriers to success are isolated and some wider issues surrounding what changes might positively affect this group are discussed.